2019
DOI: 10.3390/f10080648
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Forest Stewardship Council Certification to Sustainable Forest Management of State Forests in Selected Southeast European Countries

Abstract: In recent decades, the concept of forest certification under the Forest Stewardship Council (FSC) has been widely adopted in selected Southeast European countries (Bosnia and Herzegovina, Croatia, Serbia, and Slovenia). As sustainability is traditionally recognised as a leading principle in the forest management doctrine in these countries, the aim of this study was to understand whether, and how, FSC forest certification contributes to the sustainable management of state forests. The research was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
11
0
5
Order By: Relevance
“…In these countries FSC certification "is, to a certain extent, perceived as a guarantee for the legality of wood operations and origin." ( [15], p. 17). Since certification is desirable as a management and marketing tool but does not represent a sufficient condition for ensuring legality according to EUTR requirements, further cautions are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these countries FSC certification "is, to a certain extent, perceived as a guarantee for the legality of wood operations and origin." ( [15], p. 17). Since certification is desirable as a management and marketing tool but does not represent a sufficient condition for ensuring legality according to EUTR requirements, further cautions are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Becher (2019) found that "the imports, after the enforcement of EUTR, experienced a linear increase, or in case of tropical wood products, stagnation after a previous falling trend" ([5], p. 33). In the southern and eastern Europe, researchers mostly looked into forest certification as a mean for sustainable forest management [15,16], chain of custody certification [17] and trade of timber and timber products [18] Although EU imports of legally harvested timber increased to some extent as a consequence of implementing specific policies and regulations, it is possible that illegally harvested timber and timber products are sourced and traded domestically, or that the producer countries shifted exports to the countries/regions with less stringent regulations [19]. Among countries at risk of producing and trading in illegal timber, as well as being subject to policy side-effects, are some Western Balkan countries (e.g., Slovenia, Croatia, Serbia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the example of forests of individual countries of South-Eastern Europe (Bosnia and Herzegovina, Croatia, Serbia, Slovenia), the authors of [7] investigated the impact of forest certification under the FSC scheme on ensuring sustainable management of state forests. Based on an analysis of the inconsistencies noted in publicly available certification assessment reports and a survey of those responsible for forest certification in forestry enterprises, the researchers concluded that forest certification has a positive impact on forest management practices and sustainable forest management, especially in terms of environmental and social aspects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The forest certification process, in line with Forest Stewardship Council standards (hereinafter: FSC), has been widely adopted in the forestry sector of BiH coveringthe environmental, social, cultural and economic aspects of forest management (PEZDEVŠEK MALOVRH et al 2019a). Forest certification implies meeting a certain, predefined, sustainable forest management standard, whereas identification and proper management of high conservation value forests are one of the basic requirements (Principle 9).…”
Section: Introduction -Uvodmentioning
confidence: 99%